Antilisterial Activity of Nisin-Like Bacteriocin-Producing Lactococcus lactis subsp. lactis Isolated from Traditional Sardinian Dairy Products. (27th March 2012) - Cosentino, Sofia; Fadda, Maria Elisabetta; Deplano, Maura; Melis, Roberta; Pomata, Rita; Pisano, Maria Barbara
Abstract : With the aim of selecting LAB strains with antilisterial activity to be used as protective cultures to enhance the safety of dairy products, the antimicrobial properties of 117 Lactococcus lactis subsp. lactis isolated from artisanal Sardinian dairy products were evaluated, and six strains were found to produce bacteriocin-like substances. The capacity of these strains to antagonize Listeria monocytogenes during cocultivation in skimmed milk was evaluated, showing a reduction of L. monocytogenes counts of approximately 4 log units compared to the positive control after 24 h of incubation. In order for a strain to be used as bioprotective culture, it should be carefully evaluated for the presence of virulence factors, to determine what potential risks might be involved in its use. None of the strains tested was found to produce biogenic amines or to possess haemolytic activity. In addition, all strains were sensitive to clinically important antibiotics such as ampicillin, tetracycline, and vancomycin. Our results suggest that these bac+ strains could be potentially applied in cheese manufacturing to control the growth of L. monocytogenes .